2006
DOI: 10.1139/g05-115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ESTs from multiple Gossypium hirsutum tissues and identification of SSRs

Abstract: In an effort to expand the Gossypium hirsutum L. (cotton) expressed sequence tag (EST) database, ESTs representing a variety of tissues and treatments were sequenced. Assembly of these sequences with ESTs already in the EST database (dbEST, GenBank) identified 9675 cotton sequences not present in GenBank. Statistical analysis of a subset of these ESTs identified genes likely differentially expressed in stems, cotyledons, and drought-stressed tissues. Annotation of the differentially expressed cDNAs tentatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…We found an EST-SSR marker STV79-108, assigned to the long arm of chromosome 12 (the location of N 1 ), showed significant association with LP, LI, EPP, and MIC (Table 3). No significant hit of this primer original sequence was found in the GenBank database (Taliercio et al 2006). The allele from MD17 at this locus reduced LP and LI similar to that of the QTL on chromosome 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found an EST-SSR marker STV79-108, assigned to the long arm of chromosome 12 (the location of N 1 ), showed significant association with LP, LI, EPP, and MIC (Table 3). No significant hit of this primer original sequence was found in the GenBank database (Taliercio et al 2006). The allele from MD17 at this locus reduced LP and LI similar to that of the QTL on chromosome 26.…”
Section: Discussionmentioning
confidence: 99%
“…EST-SSR marker STV79-108, which was associated with LP, LI, and, MIC, was also tightly associated (P B 0.001, R 2 = 15.4%) with EPP. EST-SSR marker STV164-173, whose original sequence had high similarity with a gene (Pho1) coding for a-1,4-glucan phosphorylase (Taliercio et al 2006), showed a significant association with EOP (P B 0.05, R 2 = 10.3%). The gene Pho1 is related to starch metabolism (Buchner et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Pima3-79 (http:// www.cottonmarker.org/projects/hau), MGHES from EST sequences of known genes that belong to G. hirsutum (Qureshi et al 2004), MUSS/MUCS from fiber ESTs generated from G. arboreum L. cv. AKA8401 (Park et al 2005), NAU747-1387 from EST sequences transcribed in 7-10 dpa (days post anthesis) G. arboreum fibers (Han et al 2004), NAU2000-2523 from G. hirsutum fiber/ovule cDNA libraries (Han et al 2006) and STV from ESTs of multiple G. hirsutum tissues (Taliercio et al 2006). HAU042 and HAU087 were mapped in LG20 and LG31, respectively; 5 MGHES markers distributed on 5 LGs individually; 4 NAU markers from G. arboreum distributed on 4 LGs individually too; 12 NAU markers from G. hirsutum distributed on 11…”
Section: Polymorphism Revealed By Rapd and Rgapmentioning
confidence: 99%
“…raimondii, G. arboreum, G. barbadense, and G. herbaceum have been included in GenBank (http://www.ncbi.nlm.nih.gov/dbEST/). Meanwhile, great efforts have also been made to develop EST-SSRs (Qureshi et al, 2004;Taliercio et al, 2006;Guo et al, 2006) for cotton. These SSR markers have been widely applied in genetic diversity analysis (Arunita et al, 2010), construction of linkage maps (Guo et al, 2007;Lin et al, 2009), QTL mapping and marker-assisted breeding Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%